Thin Calcium Phosphate Coatings for Medical Implants - León, Betty; Jansen, John (Springer New York : Imprint: Springer, 2009)
Thin calcium phosphate coatings of about 10 µm or less can improve the bone response in orthopedic and dental implants by overcoming the drawbacks of commercially successful, thick plasma-sprayed coatings. These alternative coatings have shown better adhesion to a variety of substrates and, because of their uniformity in structure and composition, greater stability in the biological environment. Thin Calcium Phosphate Coatings for Medical Implants presents a comprehensive, state-of-the-art review of the preparation, physico-chemical properties, and in vitro and in vivo performance of these bioactive coatings, including comparisons with thick plasma-sprayed techniques. Emphasis is also placed on the benefits of special characterization techniques for this type of thin coating. This book is an essential resource not only for biomaterials researchers and their students, but also for engineers in the design, development, and manufacture of medical implants.